Photocatalytic CO2‐to‐Syngas Evolution with Molecular Catalyst Metal‐Organic Framework Nanozymes - Stanley, Philip M.; Su, Alice Y.; Ramm, Vanessa; Fink, Pascal; Kimna, Ceren; Lieleg, Oliver; Elsner, Martin; Lercher, Johannes A.; Rieger, Bernhard; Warnan, Julien; Fischer, Roland A. (Advanced materials (Weinheim), 2023)
Syngas, a mixture of CO and H2, is a high‐priority intermediate for producing several commodity chemicals, e.g., ammonia, methanol, and synthetic hydrocarbon fuels. Accordingly, parallel sunlight‐driven catalytic conversion of CO2 and protons to syngas is a key step toward a sustainable energy cycle. State‐of‐the‐art catalytic systems and materials often fall short as application‐oriented concurrent CO and H2 evolution requires challenging reaction conditions which can hamper stability, selectivity, and efficiency. Here a light‐harvesting metal‐organic framework hosting two molecular catalysts is engineered to yield colloidal, water‐stable, versatile nanoreactors for photocatalytic syngas generation with highly controllable product ratios. In‐depth fluorescence, X‐ray, and microscopic studies paired with kinetic analysis show that the host delivers energy efficiently to active sites, conceptually yielding nanozymes. This unlocked sustained CO2 reduction and H2 evolution with benchmark turnover numbers and record incident photon conversions up to 36%, showcasing a highly active and durable all‐in‐one material toward application in solar energy‐driven syngas generation. Highly active, durable, and selective catalysts for light‐driven CO2 and water conversion to value‐adding products are key toward a sustainable energy cycle. Such an all‐in‐one material is showcased, consisting of a metal‐organic framework co‐hosting two molecular catalysts. This assembly (nanozyme) harvests light, funnels energy to molecular sites, and enhances charge separation, thereby unlocking high photon efficiencies and adjustable syngas evolution.